Inoculation With Growth-Promoting Bacteria Azospirillum brasilense and Its Effects on Productivity and Nutritional Accumulation of Wheat Cultivars - Boleta, Eduardo Henrique Marcandalli [UNESP]; Shintate Galindo, Fernando [UNESP]; Jalal, Arshad [UNESP]; Santini, Jose Mateus Kondo [UNESP]; Rodrigues, William Lima [UNESP]; Lima, Bruno Horschut de [UNESP]; Arf, Orivaldo [UNESP]; Silva, Marcelo Rinaldi da [UNESP]; Buzetti, Salatier [UNESP]; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP] (Frontiers Media Sa, 2020)
Agricultural practices that allow a productive increase in a sustainable manner are becoming increasingly necessary to feed an ever-growing global population. The inoculation with Azospirillum brasilense has the potential to reduce the use of synthetic mineral fertilizers with efficient capacity to promote plant growth and increase nutrition. Therefore, this research was developed to investigate the potential use of A. brasilense to increase the accumulation of macro- and micronutrients and its influence on grain yield, plant height, and spike population in two wheat cultivars (CD1104 and CD150), under irrigated conditions in the Brazilian Cerrado. The study was carried out in a Rhodic Hapludox under a no-tillage system. The experiment was designed in randomized blocks with six replications, arranged in a 2 x 2 factorial scheme: two cultivars (CD150 and CD1104) and two levels of inoculation (control and with A. brasilense). The inoculation with A. brasilense provided greater accumulation of micronutrients in the aerial part of the wheat. In the cultivar CD1104, B and Cu had an accumulation 27.7 and 57.4% higher compared with those of the control without bacteria. In the cultivar CD150, Azospirillum increased the accumulation of B, Fe, and Mn by 43.8, 49.9, and 22%, respectively, and reduced Cu by 21.9%, compared with those of the control. The cultivar CD150 has greater efficiency to accumulate N (+35.5 kg N ha(-1)) as compared with the cultivar CD1104. Interactions between inoculation and cultivars resulted in greater accumulation of S and K in the shoot of the wheat cultivar CD150, as well greater accumulation of Cu in CD1104. In growth assessments, inoculation or cultivars did not statistically influence wheat grain yield and spike population. Howevere, for plant height, the CD1104 genotype has 13.1% bigger plant height on average than that of the CD150 genotype. Inoculation can contribute more sustainably to wheat nutrition.
Keywords: cereal; no-tillage system; Triticum aestivum L.; crop nutrition; plant-growth-promotion; sustainable-agriculture